Gambaran Durasi Penggunaan Gawai dan Jenis Aplikasi pada Siswa di SMA Batik 1 Surakarta - Ajeng Qodry Miftakhul Jannah; Siti Fatmawati (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
There are 175.4 million internet in Indonesia as of January 2020, an increase of 17% from 2019, making internet penetration in Indonesia at 64%. Applications based on the type, the are classified into several group including social media applications, game applications and e-commerce applications. This research aim to describe the duration of the use of gadgets and types of applications for students at SMA BATIK 1 Surakarta. This research method uses a descriptive survey with a sample of 302 students. The analytical method used is univariate analysis. The duration of the use of gadgets in the high category (57.9%). The duration of using social media applications is in the very high category (55.6%). Duration of use of online games in the low category (31.5%). Duration of use of e-commerce applications is in the low category (73.8%). The desription of the duration of the use of gadgets in the high category and the types of applications for the duration of the use of gadget by students at SMA BATIK 1 Surakarta that are used are social media applications, online game and e-commerce.There are 175.4 million internet in Indonesia as of January 2020, an increase of 17% from 2019, making internet penetration in Indonesia at 64%. Applications based on the type, the are classified into several group including social media applications, game applications and e-commerce applications. This research aim to describe the duration of the use of gadgets and types of applications for students at SMA BATIK 1 Surakarta. This research method uses a descriptive survey with a sample of 302 students. The analytical method used is univariate analysis. The duration of the use of gadgets in the high category (57.9%). The duration of using social media applications is in the very high category (55.6%). Duration of use of online games in the low category (31.5%). Duration of use of e-commerce applications is in the low category (73.8%). The desription of the duration of the use of gadgets in the high category and the types of applications for the duration of the use of gadget by students at SMA BATIK 1 Surakarta that are used are social media applications, online game and e-commerce.